"Slavery's Consequences Still Affect Us": Sister Souljah's No Disrespect, ?i>, Black Women's Literary Traditions and Contemporary Hip Hop Activism. (5th June 2018) - Nitzsche, Sina
Abstract : Sister Souljah is arguably one of the most important female "raptivists" in the United States. Published in 1994, her autobiography No Disrespect narrates the artist's rise from poverty to become one of the most prolific writers, educators and activists in the 1990s. Yet critics tend to overlook the autobiography's strong emphasis on activism, especially how it is embedded in larger Afro-diasporic female literary traditions. No Disrespect re-writes earlier traditions of black women's writing, visual culture and social activism in order to educate a younger generation on the ongoing need to promote racial justice. The autobiography is located in the larger context of what Paul Gilroy has called the Black Atlantic by situating it not only in American, but also in African cultural traditions. I join Reiland Rabaka and others in moving forward the field of hip hop studies by establishing more cultural, literary and visual continuities between late twentieth-century hip hop culture and earlier literary forms of Afro-diasporic expression, such as poetry and autobiography. In tracing Sister Souljah's oeuvre to the beginnings of African American women's literature in the eighteenth and nineteenth centuries, it is the aim of the article to contribute a new perspective to the origins of hip hop culture and activism beyond the twentieth and twenty-first centuries.